Chapter Diachronic evolution of the coastline of Bordj El Kiffane (Algiers, Algeria) in absence and presence of coastal protection structures - Atroune, Farid (Proceedings e report, 2020)
The coastal area of Bordj El Kiffane has experienced an artificialisation of its shoreline since 1980. This caused a remarkable decline of the shoreline. To remedy this, the solution recommended was the combination of several protection methods. In order to determine the consequence of the protective structures, a study of the historical evolution of the coastline was performed with ArcGIS and DSAS. The results allowed determining its evolutionary rates and comparing the evolutions on different periods in absence and presence of the protection structures.